Enterprise information systems and implementing IT infrastructures : challenges and issues - Parthasarathy, S., 1979- (Hershey, PA : Business Science Reference, 2010)
'This book aims at identifying potential research problems and issues in the EIS such as Enterprise Resource Planning (ERP), Supply Chain Management (SCM), and Customer Relationship Management (CRM)'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Management information systems; Information technology -- Management; Business logistics -- Data processing